Using differential mobility spectrometry to measure ion solvation: An examination of the roles of solvents and ionic structures in separating quinoline-based drugs - Liu, Chang; Le Blanc, J. C. Yves; Shields, Jefry; Janiszewski, John S.; Ieritano, Christian; Ye, Gene F.; Hawes, Gillian F.; Hopkins, W. Scott; Campbell, J. Larry (Royal Society of Chemistry, 2015)
Understanding the mechanisms and energetics of ion solvation is critical in many scientific areas. Here, we present a methodlogy for studying ion solvation using differential mobility spectrometry (DMS) coupled to mass spectrometry. While in the DMS cell, ions experience electric fields established by a high frequency asymmetric waveform in the presence of a desired pressure of water vapor. By observing how a specific ion's behavior changes between the high- and low-field parts of the waveform, we gain knowledge about the aqueous microsolvation of that ion. In this study, we applied DMS to investigate the aqueous microsolvation of protonated quinoline-based drug candidates. Owing to their low binding energies with water, the clustering propensity of 8-substituted quinolinium ions was less than that of the 6- or 7-substituted analogues. We attribute these differences to the steric hinderance presented by subtituents in the 8-position. In addition, these experimental DMS results were complemented by extensive computational studies that determined cluster structures and relative thermodynamic stabilities.
Keywords: differential mobility spectrometry